2010
DOI: 10.1175/2010waf2222378.1
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble-Based Forecast Uncertainty Analysis of Diverse Heavy Rainfall Events

Abstract: This study examines widespread heavy rainfall over 5-day periods in the central and eastern United States. First, a climatology is presented that identifies events in which more than 100 mm of precipitation fell over more than 800 000 km 2 in 5 days. This climatology shows that such events are most common in the cool season near the Gulf of Mexico coast and are rare in the warm season. Then, the focus turns to the years 2007 and 2008, when nine such events occurred in the United States, all of them leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…Based upon the results of past studies (e.g., Maddox et al 1979;Keim 1996;Schumacher and Johnson 2006;Kunkel et al 2012;Prat and Nelson 2014), it is evident that the climatology of EPEs in the SEUS is characterized by a dichotomy between the cool season (;OctoberApril) and warm season (;May-September). For these two portions of the year, EPE environments can generally be viewed as occupying different areas of a hypothetical ''dynamics-thermodynamics'' phase space such that dynamical influences [e.g., quasigeostrophic (QG) forcing of ascent, transport of water vapor by a low-level jet (LLJ)] and thermodynamical influences [e.g., convective available potential energy (CAPE); precipitable water (PW)] tend to be dominant for cool-season and warm-season events, respectively.…”
Section: B Background On Extreme Precipitation In the Seusmentioning
confidence: 99%
See 2 more Smart Citations
“…Based upon the results of past studies (e.g., Maddox et al 1979;Keim 1996;Schumacher and Johnson 2006;Kunkel et al 2012;Prat and Nelson 2014), it is evident that the climatology of EPEs in the SEUS is characterized by a dichotomy between the cool season (;OctoberApril) and warm season (;May-September). For these two portions of the year, EPE environments can generally be viewed as occupying different areas of a hypothetical ''dynamics-thermodynamics'' phase space such that dynamical influences [e.g., quasigeostrophic (QG) forcing of ascent, transport of water vapor by a low-level jet (LLJ)] and thermodynamical influences [e.g., convective available potential energy (CAPE); precipitable water (PW)] tend to be dominant for cool-season and warm-season events, respectively.…”
Section: B Background On Extreme Precipitation In the Seusmentioning
confidence: 99%
“…The SEUS can experience this class of event in all seasons in conjunction with a variety of atmospheric phenomena, such as landfalling tropical cyclones (TCs; e.g., Atallah and Bosart 2003;Shepherd et al 2007;Konrad and Perry 2010;Knight and Davis 2009;Villarini and Smith 2010), extratropical baroclinic waves and cyclones (e.g., Maddox et al 1979;Konrad 1997;Moore et al 2012), and mesoscale convective systems (MCSs; e.g., Schumacher and Johnson 2006). Furthermore, the processes associated with EPEs in the SEUS are often influenced by the unique physical geography of the region.…”
Section: A Motivation and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…4. The Gulf Coast is at risk of freshwater flooding in the cool season (Lecce 2000;Schumacher and Christopher 2010) and is home to a large potentially vulnerable human population that engages in economic activities vital to national economies (Boruff, Emrich, and Cutter 2005).…”
Section: Study Regionmentioning
confidence: 99%
“…The European Centre for Medium-Range Weather Forecasts (ECMWF) Ensemble Prediction System (EPS) has been used to explore rainfall predictability, and the results showed that precipitation is more predictable during the winter than in the summer and rainfall associated with tropical cyclones is more predictable than the warm-season cases (Buizza et al, 1999;Mullen and Buizza, 2001;Schumacher and Davis, 2010). ECMWF EPS was also used to identify key factors influencing the May 2010 extreme rainfall in Tennessee and Kentucky (Lynch and Schumacher, 2014) and longer-term warm-season rainfall (Schumacher, 2011).…”
Section: Introductionmentioning
confidence: 99%